Social Aspects in the Kingdom of Mali Through Ibn Battuta's book Tuhfat Alnuddar in Garaeb Al Amsar Wa Ajaeb Al Asfar - Zainab Abdul Jabbar; Abbas Al Mafraji (College of Education for Women, 2019)
Social Aspects in the Kingdom of Mali Through Ibn Battuta's book Tuhfat   Alnuddar  in  Garaeb  Al Amsar  Wa  Ajaeb  Al  Asfar